2019
DOI: 10.3390/ma12132065
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of High Vacuum Die-Cast AlSiMgMn Alloys at as-Cast and T6-Treated Conditions

Abstract: Al–Si–Mg based alloys can provide high strength and ductility to satisfy the increasing demands of thin wall castings for automotive applications. This study has investigated the effects of T6 heat-treatment on the microstructures, the local mechanical properties of alloy phases and the fracture behavior of high vacuum die-cast AlSiMgMn alloys using in-situ scanning electron microscopy (SEM) in combination with nano-indentation testing. The microstructures of the alloys at as-cast and T6 treated conditions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In a study of the effect of T6 heat treatment on the alloy AlSi11MgMn, Liu et al [39] observed a decrease in UTS, while the elongation increased for alloys produced by VHPDC. In this alloy, the microcracks formed near the large α-Fe intermetallic and not due to the eutectic Si particles.…”
Section: Microstructure Of the Alsi9cu3(fe) Cast By Vhpdc (A) Skin La...mentioning
confidence: 99%
“…In a study of the effect of T6 heat treatment on the alloy AlSi11MgMn, Liu et al [39] observed a decrease in UTS, while the elongation increased for alloys produced by VHPDC. In this alloy, the microcracks formed near the large α-Fe intermetallic and not due to the eutectic Si particles.…”
Section: Microstructure Of the Alsi9cu3(fe) Cast By Vhpdc (A) Skin La...mentioning
confidence: 99%
“…Mechanical properties of the aluminum-silicon alloys, in particular the tensile strength, ductility, hardness, and fatigue, are * E-mail: kchapparao@gmail.com strongly dependent on the dendritic structure, and on primary Al α-grains in the respective microstructures [3,4]. Kori et al [5] observed that grain refinement is the most effective process to achieve homogeneously distributed small equiaxed grains, and in addition, following this process results in a high strength-to-weight ratio, excellent castability, and other desired properties [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…During the transition of the melt through then cross-sections and complex shapes of the cast, more significant mixing of gases and vapors with melt occurs [Cao 2019]. One of the possibilities to prevent mixing of the melt with gases is a suitable design of the gating system, starting with the correct design of the runners, through the design of the ingates to the correct design of the ventilation system [Meethum 2017, Otsuka 2014]. Another possibility of elimination of the porosity in casts is the correct setting of technological parameters of the casting cycle [Pasko 2014].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, high pressure values support faster wearing off the mold and increased demands on design and quality of the mold material [Nova 2012, Ruzbarsky 2014. In conventional HPDC technology i tis necessary to find a compromise between the design of the gating system and the setting of technological parameters of casting with respect to the melt flow regime through the runners and perfect discharge of the gases from mold cavity in front of the advancing melt stream [Liu 2018]. A progressive development of the HPDC is the incorporation of a vacuum device into the process to extract gases and vapors from the mold cavity in front of the advancing melt stream.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation